Navigating HSK level 5 challenges: dual perspectives from Thai undergraduates and Chinese lecturers - Yang Yang; Yanchinda Jirawit (Language Testing in Asia)
Abstract The ever-growing significance of Chinese language education in Thailand highlights the strategic importance of achieving higher levels, specifically Hanyu Shuiping Kaoshi (HSK) level 5, as a key steppingstone for future academic and career development. For the majority of Thai undergraduates, nevertheless, efficient test preparation encounters systemic, pedagogical, and motivational challenges. These are further exacerbated by misaligned institutional frameworks and a lack of coherence between HSK 5 preparation and general educational objectives. Based on Self-Determination Theory (SDT) and Cognitive Load Theory (CLT), the current study investigates the role of motivational orientations, cognitive processing constraints, and institutional frameworks in students' preparation and performance in the HSK exam. The study aims to (1) examine Thai undergraduates' learning behaviors, motivation, and psychological challenges in HSK level 5 preparation. (2) Determine the efficacy and accessibility of teaching methodologies and learning resources in addressing the needs of the students and enhancing examination performance. (3) Investigate Chinese instructors’ views of pedagogical issues and instructional methods to better facilitate HSK level 5 preparation. The present research adopted a mixed-methods design to explore the root causes behind such difficulties by administering a survey for 139 undergraduate students, who were sampled using stratified random sampling to achieve representativeness across levels of proficiency and semi-structured interviews with 12 Chinese lecturers selected by purposive sampling to provide rich insights into teaching practices and systemic gaps. The findings of this study suggest the integration of structural reforms in university-level Chinese education: the introduction of HSK 5 as a prerequisite for graduation, better access to updated resources, mock examinations, and learner-centered pedagogic approaches. It is also recommended to provide mechanisms of financial and psychological support to overcome such barriers, thus providing actionable insights into the advancement of Chinese language education in Thailand and its academic, cultural, and economic connectivity with China.